Roles of accessibility, connectivity and spatial interdependence in realizing the economic impact of high-speed rail: Evidence from China - Jiao, Jingjuan; Wang, Jiaoe; Zhang, Fangni; Jin, Fengjun; Liu, Wei (Transport policy, 2020)
The rapid development of high-speed rail (HSR) in China has raised questions about its implications for regional economic growth. Most existing studies take an aggregate approach to quantify the economic impacts of HSR entrance primarily by inspecting the effect of the dummy variable which reflects the existence of HSR service. This paper takes one step further to investigate how network effects play a role in realizing these impacts. In particular, the effects of location endowment characteristics (evaluated by accessibility and connectivity) enabled by HSR development and the spatial interdependent effects (reflected by neighbors’ impacts) are examined. Based on the panel data from China during 2007–2015, we find that when these new factors are taken into account, the effect of the HSR dummy variable (reflecting the existence of HSR service) on regional economic growth is insignificant. On the contrary, the effects of both location endowment measurements, accessibility and connectivity in the railway network, and neighboring effects are significant. These important observations imply that: (1) The economic impact of HSR is largely accomplished by improving accessibility and connectivity in the railway network rather than an isolated presence of HSR infrastructure; (2) The accessibility and connectivity of neighboring cities impact the economic growth of one another; (3) HSR development has generated uneven economic growth concerning the cities in different geographic regions and with different population scales; (4) There is a mismatch between where the accessibility improves the most and where unit improvement generates the largest economic growth; (5) Accessibility and connectivity improvement by railway resulted in a smaller increase in economic growth than that of highway, but larger than those by air and water. These implications shed light on policies regarding multi-modal transport system planning, transport infrastructure investment, and HSR development and operations. •Roles of network effects in the economic impact of HSR are identified.•Benefit of HSR is primarily realized by improving accessibility and connectivity.•Accessibility and connectivity of neighbors impact the economic growth of one another.•Spatial mismatch exists in maximums of accessibility change and economic impact.•Effect of HSR on economic growth is smaller than highway, larger than air and water.